Current situation of shopping centres in China: Case studies of LIVAT and K11 - Shi, Han (2018)
Along with the rapid growth of China's economy and the positive impact of economic policies, China's shopping centers have experienced a period of rapid development. This dissertation aims to achieve two objectives. The first one is providing a current industrial picture of shopping centers in China for potential investors and related practitioners. The PESTEL and Porter's five forces models will be employed to analyze and describe the macro as well as the micro environment of Chinese shopping centers. The second objective is helping readers to have a more intuitive understanding of Chinese shopping centers with more details and pictures. The researcher will combine 4P marketing theory and the choice criteria in shopping mall selection as a framework to analyze two cases: K11 and LIVAT which are not only the outstanding representatives of the industry but also set examples of differentiated operations for the existing shopping centres in China.